AN ANALYSIS OF MORPHEME IN BLACK PANTHER MOVIES: MORPHOLOGICAL APPROACH - Muhammad Arsyad Hakim; Ruben Leopoldo Mantiri; Nurma Dhona Handayani (Proceeding of Undergraduate Conference on Literature, Linguistic, and Cultural Studies, 2022)
This study aims to identify the types of morphemes and the category of the bound morphemes used in Black Panther Movie, the researcher chose to analyze the black panther morpheme because it is interesting, the language in the film is not only English, and the words used are simple. Has a complex and compelling storyline. The film then shone at the Oscars because many people enjoyed it and wanted to see it. And, when considering the issues and perspectives presented, Black Panther was so successful that it was accepted by the world and received numerous awards. The researchers used observation technique to collect the data by watching the movie, taking notes, and classifying the data into each category. The data then were analyzed qualitatively through three stages, namely data reduction, data display, and verification, after gathering all the data from the Black Panther film, the researchers will choose and simplify the information that will be used in the analysis. The data were be organized and classified into the derivational and inflectional morphemes after the reduction procedure is complete in order to be presented. After completing the processes, the researcher confirmed the data in accordance with the study's objectives and draw conclusions from the already-analyzed data. Categorizing the data into certain types of morphemes is based on Booij, who classified type of morpheme into free morphemes and bound morphemes. Further data classification whether the data is included in free morpheme or bound morpheme is based on Booji, Salzmann, and Yule. This study found 341 free morphemes and 76 bound morphemes in Black Panther Movie, which the number of inflectional morphemes (56 data) are more than derivational morphemes (20 data). Most of the data found in this study are free morphemes, because in the black panther film they talk more about the problems of people who are doing war.